A Controlled and Comparative Study on Vatari Guggulu and Shiva Guggulu in the Treatment of Gridhrasi. - CS, Veena; Bhat, Roopa (International Research Journal of Ayurveda & Yoga, 2021)
A single blind controlled comparative clinical study with pre test and post test design to evaluate the therapeutic efficacy of Shiva Guggulu and Vatari Guggulu in the management of Gridhrasi. The study carried out at Dhanvantari Ayurveda medical college Hospital; Siddapur, Uttara Karnataka. 40 patients suffering from Gridhrasi / SCIATICA of either sex were selected for the study were treated under two groups; A and B. Group A with oral administration of Shiva Guggulu, in a dose of 500 mg after food twice a day with sukhoshna jala as anupana and the same is continued for 30 days. Group B with oral administration of Vatari Guggulu, in a dose of 500 mg after food twice a day with sukhoshna jala as anupana for 30 days. The response following the intervention was assessed on 1st, 15th, 21st, and 30th days to find out the progress of the Condition in both the groups.Final conclusion of this controlled comparative clinical study says Group A is more effective than Group B (Shiva guggulu is more effective than Vatari guggulu) in the management of Gridhrasi.